2021
DOI: 10.4236/ce.2021.129158
|View full text |Cite
|
Sign up to set email alerts
|

Research and Practice of Hybrid Teaching Mode of “Film and Television Production Technology and Art” Course Based on OBE Concept

Abstract: The OBE education model is a kind of "learning output" oriented education model. In the construction of the course "Film and Television Production Technology and Art", the OBE education concept is effectively integrated with the hybrid teaching mode. The article elaborates this topic from the construction of the teaching model, the effectiveness of the practice, and the matters that need attention in the practice. After practice, it is found that the model can effectively improve the teaching quality of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…e pretest t-test students' interest in learning showed that the pretest Sig (double-tailed) value was >0.05, indicating that there was no difference between student satisfaction in the laboratory and in the control room Before the test. In the event of a test discrepancy after the survey data have been provided, the Sig value >0.05 and the difference between the two samples can be detected in the same way [1]. After eliminating the effects on students' early learning interest after the experiment, the average of the pilot classes was 4.14 and the average of the control classes was 3.92. e average laboratory score is higher than that of the control room.…”
Section: Analysis On the Effect Of Learning Interest Dimensionmentioning
confidence: 88%
See 2 more Smart Citations
“…e pretest t-test students' interest in learning showed that the pretest Sig (double-tailed) value was >0.05, indicating that there was no difference between student satisfaction in the laboratory and in the control room Before the test. In the event of a test discrepancy after the survey data have been provided, the Sig value >0.05 and the difference between the two samples can be detected in the same way [1]. After eliminating the effects on students' early learning interest after the experiment, the average of the pilot classes was 4.14 and the average of the control classes was 3.92. e average laboratory score is higher than that of the control room.…”
Section: Analysis On the Effect Of Learning Interest Dimensionmentioning
confidence: 88%
“…PBL teaching mode not only mobilizes students' learning initiative and gives students sufficient learning resources and a good learning atmosphere, but also enables students to obtain a sense of achievement in handson practice and exploration, so as to stimulate students' interest in learning information technology. In the traditional teaching mode, teachers only talk about the animation (1) Master and understand the different knowledge and skills of graphic elements, film editing elements and button elements (2) Master the method of creating and editing components (3) Understand the library and learn to apply the library to manage components Process and method (1) In autonomous learning, students can learn the principle, manufacturing method, process and method of components (2) rough the form of group discussion, students can learn new knowledge and skills and begin to adapt to new learning forms…”
Section: Analysis On the Effect Of Learning Interest Dimensionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to make learning English better help students work in the professional field, it is necessary to enhance students' English level and improve students' listening, speaking, reading, and writing ability. The development of English proficiency will not solely facilitate students at work [ 17 ]. It can be seen that the cultivation of English ability cannot simply improve the skill quality of scholars, but must be combined with the cultivation of humanistic quality.…”
Section: Methods Of College English Multimodal Teachingmentioning
confidence: 99%
“…Advertising creativity is abbreviated as AC, which is advertisement creativity. It combines business behavior and the art of thinking and is a key factor in the success of product marketing [19]. Excellent advertising ideas immediately impact the senses of consumers and cause strong emotional reactions, which are effective factors to promote consumer behavior.…”
Section: Creative Effect Of Film and Television Advertisingmentioning
confidence: 99%